Celebrity impact on young adults purchasing Behaviour / Siti Fariedah Abdullah - Abdullah, Siti Fariedah (UITM Sarawak,Kampus Samarahan, 2015)
This study aim to investigate the impact of celebrity endorsement to the young adults purchasing behavior. Nowadays there are large numbers of brands available in the market so there is a crucial need for the company to distinguish themselves from the competitors. The most familiar ways to distinguish them is by investing on celebrity to endorse their product. This study focus on 1) To identify the celebrity attributes that affect young adult purchasing behavior and 2) To determine which of these attributes give the most impact on young adult purchasing behaviour. The target population of this study was 120 respondents female and male on age 20 to 40 years old. Primary data will be collected through self administered questionnaire and secondary data was collected through journals and websites. The data was analyze y using SPSS 16 which will be presented by use of table, bar chart, frequency distribution tables, pie chart and graphs. This provide the generalization of the findings on the relationship between celebrity endorsement with young adults purchasing behavior. In addition, this study also use reliability analysis, Regression Analysis and Correlation analysis in order to determine the level of strength each of the attributes with the young adult's purchasing behaviour. The findings of this study will provide further insight to the marketers and researcher for them to plan the strategies better in order to increase brand awareness and help in future researcher literature review.